Morphological evaluation and clinical significance of proximal femoral dimensions among Southern Nigerian population - Obikili, Emmanuel N.; Omotoso, Dayo R. (International Journal of Research in Medical Sciences, 2020)
Background: Anthropometric studies are vital in evaluation and description of morphological characteristics of body tissues of living individuals or dead remains. This study was done to evaluate proximal femoral dimensions and to describe sexual or bilateral dimorphism among Southern Nigerians. Methods: This study involved 500 pelvic radiographs showing proximal aspects of right and left femurs of Southern Nigerians (including 250 males and 250 females) between ages 25 to 55 years. Measurements taken on radiographs include transverse diameter and vertical diameter of femoral head, neck diameter (ND), neck length (NL) and proximal shaft diameter. Bilateral measurements were recorded and average values evaluated. Data were analyzed using IBM-statistical package for social sciences (SPSS) (version 20) and statistical comparison was done using analysis of variance (ANOVA) with p<0.05 regarded as statistically significant level. Results: Proximal femoral dimensions showed non-significant bilateral differences with right side having higher values in all parameters except NL in males and ND in females. Also, mean values for TD (5.39±0.25 and 4.28±0.21), VD (5.01±0.21 and 4.58±0.19), ND (4.03±0.22 and 3.61±0.18), NL (2.08±0.11 and 1.79±0.10) for male and females subjects respectively showed sexual dimorphism in all parameters with males having significantly (p<0.05) higher values than females. Conclusions: The femur is an important bone in human body that plays crucial morphological and physiological role and offers prominent anthropometric value.